Collaborative Governance Policing in Handling Illegal Coal Mining Cases in Muara Enim Regency - Aldila, Roy Prima (Jurnal Sosial Teknologi, 2025)
Illegal coal mining (PETI) poses significant environmental, legal, and economic threats in Muara Enim Regency, South Sumatra. This study explores the application of collaborative governance policing in addressing this persistent issue. The research aims to analyze (1) the characteristics of illegal coal mining in Muara Enim, (2) the implementation of multi-stakeholder collaborative policing by the Muara Enim Police, and (3) the strategic expectations for effective law enforcement and community engagement. Utilizing a qualitative approach with a case study method, data were gathered through in-depth interviews, field observations, and document analysis involving police officers, local government agencies, and community stakeholders. The findings reveal a shift in illegal mining practices from manual labor to the use of heavy machinery, increasing the scale and impact of environmental degradation. The formation of a multi-agency Task Force led by the Muara Enim Police demonstrates a positive step, although challenges remain due to limited accessibility, coordination gaps, and community economic dependence on mining. The research underscores the need for strengthened predictive policing strategies, e-policing initiatives, and digital citizen engagement tools. Strategic collaboration following the Pentahelix model—government, academia, business, community, and media—is essential to achieving sustainable enforcement and prevention. This study contributes to the development of a contextualized, forward-looking collaborative policing framework in mining-intensive regions of Indonesia.